To Improve A Performance of Induction Motor Using PBO-ANFIS - Kumar Bindal, Ranjit; Kaur, Inderpreet (International Journal of Engineering and Technology, 2018)
The performance of intelligent control Adaptive Neuro Fuzzy Inferences system (ANFIS) with Pollination based optimization (PBO) is presented for the speed and torque control of an induction motor using direct torque control in detail. Here a DTC method is being presented and analyzed. This technique consists of a neural network controller, pollination based optimization, a reference model, and an algorithm   for changing the ANFIS weights altogether to limit the speed of the ac machine. A PBO-ANFIS gives better speed control, dynamic behaviour and superior characteristics of the three-phase ac motor with DTC. In this paper, the conventional controller technique is replaced by PBO-ANFIS controller. The proposed technique is compared with the conventional technique and from the comparative study  it is seen that the rise time is reduced from 260ms to 1.266ms, settling time is reduced by 725ms to 12.76ms and transient time is reduced by 520ms to 10.99ms times and torque ripples are reduced by 6%.